Evaluation of nurse triage in a British accident and emergency department. Issue 6831 (4th April 1992) - George, S.; Read, S.; Westlake, L.; Williams, B.; Fraser-Moodie, A.; Pritty, P.
Abstract : OBJECTIVE–To compare formal nurse triage with an informal prioritisation process for waiting times and patient satisfaction. SETTING–Accident and emergency department of a district general hospital in the midlands in 1990. DESIGN–Patients attending between 8:00 am and 9:00 pm over six weeks were grouped for analysis according to whether triage was operating at time of presentation and by their degree of urgency as assessed retrospectively by an accident and emergency consultant. PATIENTS–5954 patients presenting over six weeks. MAIN OUTCOME MEASURES–Time waited between first attendance in the department and obtaining medical attention, and patient satisfaction measured by questionnaire. RESULTS–Complete data on waiting time were collected on 5037 patients (85%). Only 1213 of the 2515 (48%) patients presenting during the triage period were seen by a triage nurse. Patients in the triage group waited longer than those in the no triage group in all four retrospective priority categories, though differences were significant for only the two most urgent categories (difference in median waiting time 10.5 (95% confidence interval 3.5 to 14) min for category 1 and 8.5 (3 to 12) min for category 2). Responses to the patient satisfaction questionnaire were similar in the two groups except for the question relating to anxiety relating to pain. CONCLUSIONS–This study fails to show the benefits claimed for formal nurse triage. Nurse triage may impose additional delay for patient treatment, particularly among patients needing the most urgent attention.